Adjuvant nivolumab versus ipilimumab in resected stage IIIB-C and stage IV melanoma (CheckMate 238): 4-year results from a multicentre, double-blind, randomised, controlled, phase 3 trial - Ascierto, Paolo A; Del Vecchio, Michele; Mandalá, Mario; Gogas, Helen; Arance, Ana M; Dalle, Stephane; Cowey, C Lance; Schenker, Michael; Grob, Jean-Jacques; Chiarion-Sileni, Vanna; Márquez-Rodas, Iván; Butler, Marcus O; et al. (Lancet oncology, 2020)
BACKGROUND: Previously, findings from CheckMate 238, a double-blind, phase 3 adjuvant trial in patients with resected stage IIIB-C or stage IV melanoma, showed significant improvements in recurrence-free survival and distant metastasis-free survival with nivolumab versus ipilimumab. This report provides updated 4-year efficacy, initial overall survival, and late-emergent safety results. METHODS: This multicentre, double-blind, randomised, controlled, phase 3 trial was done in 130 academic centres, community hospitals, and cancer centres across 25 countries. Patients aged 15 years or older with resected stage IIIB-C or IV melanoma and an Eastern Cooperative Oncology Group performance status of 0 or 1 were randomly assigned (1:1) to receive nivolumab or ipilimumab via an interactive voice response system and stratified according to disease stage and baseline PD-L1 status of tumour cells. Patients received intravenous nivolumab 3 mg/kg every 2 weeks or intravenous ipilimumab 10 mg/kg every 3 weeks for four doses, and then every 12 weeks until 1 year of treatment, disease recurrence, unacceptable toxicity, or withdrawal of consent. The primary endpoint was recurrence-free survival by investigator assessment, and overall survival was a key secondary endpoint. Efficacy analyses were done in the intention-to-treat population (all randomly assigned patients). All patients who received at least one dose of study treatment were included in the safety analysis. The results presented in this report reflect the 4-year update of the ongoing study with a database lock date of Jan 30, 2020. This study is registered with ClinicalTrials.gov, NCT02388906. FINDINGS: Between March 30 and Nov 30, 2015, 906 patients were assigned to nivolumab (n=453) or ipilimumab (n=453). Median follow-up was 51·1 months (IQR 41·6-52·7) with nivolumab and 50·9 months (36·2-52·3) with ipilimumab; 4-year recurrence-free survival was 51·7% (95% CI 46·8-56·3) in the nivolumab group and 41·2% (36·4-45·9) in the ipilimumab group (hazard ratio [HR] 0·71 [95% CI 0·60-0·86]; p=0·0003). With 211 (100 [22%] of 453 patients in the nivolumab group and 111 [25%] of 453 patients in the ipilimumab group) of 302 anticipated deaths observed (about 73% of the originally planned 88% power needed for significance), 4-year overall survival was 77·9% (95% CI 73·7-81·5) with nivolumab and 76·6% (72·2-80·3) with ipilimumab (HR 0·87 [95% CI 0·66-1·14]; p=0·31). Late-emergent grade 3-4 treatment-related adverse events were reported in three (1%) of 452 and seven (2%) of 453 patients. The most common late-emergent treatment-related grade 3 or 4 adverse events reported were diarrhoea, diabetic ketoacidosis, and pneumonitis (one patient each) in the nivolumab group, and colitis (two patients) in the ipilimumab group. Two previously reported treatment-related deaths in the ipilimumab group were attributed to study drug toxicity (marrow aplasia in one patient and colitis in one patient); no further treatment-related deaths were reported. INTERPRETATION: At a minimum of 4 years' follow-up, nivolumab demonstrated sustained recurrence-free survival benefit versus ipilimumab in resected stage IIIB-C or IV melanoma indicating a long-term treatment benefit with nivolumab. With fewer deaths than anticipated, overall survival was similar in both groups. Nivolumab remains an efficacious adjuvant treatment for patients with resected high-risk melanoma, with a safety profile that is more tolerable than that of ipilimumab. FUNDING: Bristol Myers Squibb and Ono Pharmaceutical.
Keywords: Nivolumab; Aged; Treatment Outcome; melanom; Neoplasm Staging; lidé středního věku; senioři; nežádoucí účinky léčiv; Antibodies, Monoclonal; lidé; staging nádorů; Middle Aged; lokální recidiva nádoru; Neoplasm Recurrence, Local; antigen CTLA-4; CTLA-4 Antigen; Female; výsledek terapie; Disease-Free Survival; Ipilimumab; Male; ženské pohlaví; Humans; mužské pohlaví; Double-Blind Method; Drug-Related Side Effects and Adverse Reactions; nivolumab; ipilimumab; přežití bez známek nemoci; Melanoma; monoklonální protilátky; dvojitá slepá metoda